Diagnosis and treatment of Malassezia dermatitis in a Persian cat - Chairunnisa, Arvia; Nadya, Siti Faridha Amalia Ihsanu; Windria, Sarasati; Rifki, Prananda Eka; Wuri, Rahmitiana (ARSHI Veterinary Letters, 2024)
The presence of Malassezia fungus on the skin, in both normal and excessive amounts, can activate the skin's immune system in cats. This paper reports a case of a seven-year-old Persian cat named Imo, who presented with eye pain and symptoms of dermatitis during a physical examination. A supporting examination, including a combo test kit and cytology, led to a diagnosis of Malassezia dermatitis. The therapy provided involved cleaning and compressing the wound with a saline solution containing NaCl, administering itraconazole and an oxyfresh water additive, injecting marbofloxacin subcutaneously, and applying vaseline topically. The patient showed noticeable improvement in wound healing within 24 days of hospitalization